Nutritional parameters are associated with mortality in acute kidney injury - Berbel, Marina Nogueira [UNESP]; Goes, Cassiana Regina de [UNESP]; Balbi, André Luis [UNESP]; Ponce, Daniela [UNESP] (Hospital Clinicas, Univ Sao Paulo, 2014)
OBJECTIVE: The objective of this study was to perform a nutritional assessment of acute kidney injury patients and to identify the relationship between nutritional markers and outcomes.METHOD: This was a prospective and observational study. Patients who were hospitalized at the Hospital of Botucatu School of Medicine were evaluated between January 2009 and December 2011. We evaluated a total of 133 patients with a clinical diagnosis of acute kidney injury and a clinical presentation suggestive of acute tubular necrosis. We explored the associations between clinical, laboratory and nutritional markers and in hospital mortality. Multivariable logistic regression was used to adjust for confounding and selection bias.RESULTS: Non-survivor patients were older (67 +/- 14 vs. 59 +/- 16 years) and exhibited a higher prevalence of sepsis (57.1 vs. 21.4%) and higher Acute Tubular Necrosis-Individual Severity Scores (0.60 +/- 0.22 vs. 0.41 +/- 0.21) than did survivor patients. Based on the multivariable analysis, laboratorial parameters such as blood urea nitrogen and C-reactive protein were associated with a higher risk of death (OR: 1.013, p = 0.0052; OR: 1.050, p = 0.01, respectively), and nutritional parameters such as low calorie intake, higher levels of edema, lower resistance based on bioelectrical impedance analysis and a more negative nitrogen balance were significantly associated with a higher risk of death (OR: 0.950, p = 0.01; OR: 1.138, p = 0.03; OR: 0.995, p = 0.03; OR: 0.934, p = 0.04, respectively).CONCLUSIONS: In acute kidney injury patients, a nutritional assessment seems to identify nutritional markers that are associated with outcome. In this study, a low caloric intake, higher C-reactive protein levels, the presence of edema, a lower resistance measured during a bioelectrical impedance analysis and a lower nitrogen balance were significantly associated with risk of death in acute kidney injury patients.
Keywords: Acute Kidney Injury; Anthropometry; Nitrogen Balance; Nutrition; Nutrition Assessment